Base‐Mediated Defluorosilylation of C(sp2)−F and C(sp3)−F Bonds. (17th January 2019) - Liu, Xiang‐Wei; Zarate, Cayetana; Martin, Ruben
Abstract: The ability to selectively forge C–heteroatom bonds by C−F scission is typically accomplished by metal catalysts, specialized ligands and/or harsh reaction conditions. Described herein is a base‐mediated defluorosilylation of unactivated C(sp 2 )−F and C(sp 3 )−F bonds that obviates the need for metal catalysts. This protocol is characterized by its simplicity, mild reaction conditions, and wide scope, even within the context of late‐stage functionalization, constituting a complementary approach to existing C−Si bond‐forming protocols.